COLLABORATIVE GOVERNANCE DALAM PENGGUNAAN KENDARAAN BERMOTOR BERBASIS LISTRIK DI LOTA PEKANBARU TAHUN 2022 - Wati, Meny Wenia; Susanto, Agus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Air pollution is one of the problems regarding poor air quality, most air pollution is contributed by motorized vehicles, the use of fuel oil used by motorized vehicles is the main cause of air pollution. According to Indonesian data, 70% of contributors to air pollution in Pekanbaru are motorized vehicles. The Pekanbaru city government is given the challenge to realize electric vehicles in the Pekanbaru community regarding the use of electric vehicles, and the government needs to collaborate in the development of electric vehicles to reduce air pollution. In this case, the researcher aims to describe collaborative governance in the use of electric-based motorized vehicles in Pekanbaru in 2022. In achieving this research objective, the researcher used Ansell and Gash's theory about Collaborative Governance. The research method used was a qualitative method by explaining descriptive data, then the research location was in Pekanbaru city government office, Riau Province Energy and Mineral Resources (ESDM) Service, and PLN WRKR Pekanbaru. The research results found that the collaborative process carried out by the Pekanbaru government regarding the use of electric vehicles was going well. Steps such as price reductions, tax cuts, and collaboration between the Pekanbaru city government, PLN WRKR, the ESDM Department and two other stakeholders. However, Collaborative governance is not yet fully running well because some Pekanbaru people do not fully understand the benefits of electric vehicles, each party involved in the collaboration coordinates with each other, therefore the author draws the following conclusions Collaborative Governance in the use of electric-based motorized vehicles in Pekanbaru in 2022 it is said to have been successful. However, it is not yet running optimally because there are still factors that hinder the use of electric-based motorized vehicles in Pekanbaru. Keywords: Collaborative Gobernance, Policy and Electric Vehicles.